Spirobi[dibenzo[b, e][1, 4]azasiline]: a novel platform for host materials in highly efficient organic light-emitting diodes. Issue 5 (15th January 2018) - Liu, Xiang-Yang; Tang, Xun; Zhao, Yue; Zhao, Danli; Fan, Jian; Liao, Liang-Sheng
Abstract : Spirobi[dibenzo[ b, e ][1, 4]azasiline] molecular platform was used as a building block to construct host materials for highly efficient RGB phosphorescent OLEDs. Abstract : A novel spiro-type material (5 H, 5′ H -10, 10′-spirobi[dibenzo[ b, e ][1, 4]azasiline]-5, 5′-diyl)bis((4-methoxyphenyl)-methanone) (SDBSO) was designed and synthesized. The introduction of spirobi[dibenzo[ b, e ][1, 4]azasiline] causes the material to retain high triplet energy (over 3.10 eV). In addition, owing to its highly steric and rigid structure and spiro-linkage, SDBSO exhibited good thermal stability and suitable frontier molecular orbital (FMO) energy levels. The RGB (blue, green, and red) three-color phosphorescent organic light-emitting diodes with SDBSO as the host material were fabricated and maximum external quantum efficiencies of over 20% were achieved for the green and red devices with relatively flat roll-off, indicating its potential utility as a host-building block for highly efficient PHOLEDs.